THE EFFECT OF USING KAHOOT! APPLICATION ON STUDENTS' VOCABULARY - Raihana Herlis Syahputri; Lenny Solo (Department of English Education, Universitas Panca Sakti Bekasi, 2022)
The aim of this study was to determine the effect of using Kahoot! application on students’ vocabulary at seventh grade of SMPN 6 Bekasi. This research was conducted in the academic year 2021/2022. This research method uses an experimental design. The sample of this study consisted of 40 students at the seventh grade and divided the students into 2 classes, namely the experimental class and the control class. This data was obtained by conducting a post test on the students. The post test for the experimental class is given through the Kahoot! application while the control class is given via Google Form. The reliability test analysis was carried out in this study using the SPSS program, with a value of 0.609 it can be said that the test is valid. The results of the post-test from both classes showed that the score of the experimental class was 1900 and the control class was 1470 which means there is a difference between the results of the post-test control class and the experimental class. This shows that the t test value has a significance level